Series Active Variable Geometry Suspension application to chassis attitude control - Arana,C; Evangelou,SA; Dini,D (IEEE/ASME Transactions on Mechatronics, 2015)
This paper explores the application of the recently introduced Series Active Variable Geometry Suspension (SAVGS) to the control of chassis attitude motions and the directional response of cars. A co-design methodology, involving a component dimensioning framework and a multi-objective control scheme, is developed to maximize the SAVGS control capabilities while respecting vehicle and actuator design constraints. The dimensioning framework comprises: a steady-state mathematical model based on the principle of virtual work; a parameter sensitivity analysis that sheds light on the dependencies that exist between the properties of the passive suspension, the SAVGS and the chassis; and an algorithm to size the main SAVGS components for any given vehicle and steady-state performance objectives. The general multi-objective control scheme is presented for general application, and the particular case of combined chassis attitude control and overturning couple distribution control is developed in detail. The proposed scheme is subsequently applied to a high performance sports car and a fully laden SUV and tested under a wide range of operating conditions through the simulation of standard open-loop maneuvers. Results demonstrate the SAVGS potential to favorably regulate the attitude motions and directional response in both vehicle classes.